Uterine Rupture with Massive Late Postpartum Hemorrhage due to Placenta Percreta Left Partially In Situ. (10th December 2013) - Salman, Mehmet Coskun; Calis, Pinar; Deren, Ozgur
Abstract : Placental adhesive disorders involve the growth of placental tissue into or through the uterine wall. Among these disorders, placenta percreta is the rarest one. However, it may cause significant complications. This report aimed to report a neglected patient with placenta percreta who developed uterine rupture with life-threatening late postpartum intra-abdominal hemorrhage. On admission, the patient had acute abdomen with moderate abdominal distention and was subjected to emergency laparotomy. A full-thickness defect of the anterior uterine wall involving the hysterotomy site was seen. Placental tissues occupied both sides of the incision and posterior bladder wall was also invaded by placenta. Total abdominal hysterectomy with partial resection of the posterior bladder wall was performed.